Early outcomes of mitral valvuloplasty by minimally invasive surgery or sternotomy. (September 2020) - Huang, Huan-lei; Yan, Qian; Xie, Xu-jing; Zhou, Kan; He, Biao-chuan; Yang, Liang
Background: Disagreement exists regarding methods for repair of the mitral valve. We compared early outcomes of mitral valvuloplasty by a minimally invasive technique and by a median sternotomy. Methods: The data of 507 patients (mean age 47.9 ± 15.2 years) undergoing mitral valvuloplasty from January 2015 to June 2018 were analyzed retrospectively. In the study group ( n  = 225), mitral valvuloplasty via a totally thoracoscopic approach was performed by a single surgeon. In the control group ( n  = 282), mitral valvuloplasty via the traditional median sternotomy was carried out by other cardiac surgeons in our hospital. Clinical data, surgical results, and follow-up findings in the two groups were comparatively analyzed. Results: In the study group, the blood transfusion rate (5.3% vs. 20.9%, p  < 0.05) and incidences of poor wound healing (0 vs. 5.3%, p  < 0.05) and respiratory tract infection (4.4% vs. 16.3%, p  < 0.05) were lower, and postoperative hospitalization was shorter (5.9 ± 4.0 vs. 10.7 ± 8.4 days, p  < 0.05). Within 30 days after surgery, no patient died in the study group while one died in the control group. The duration of follow-up was 12–36 months (mean 22.9 ± 8.8 months). During follow-up, there were 1 and 0 cases of redo surgery and 1 and 3 deaths in the study group and control group, respectively. Conclusion: Mitral valvuloplasty via a minimally invasive approach is superior to the traditional median sternotomy in terms of early outcomes, especially when performed by experienced surgeons.